Risk Control Of Onion (Allium ascalonicum L.) Production On Surjan Land - Aliudin Aliudin; Aris Supriyo Wibowo; Setiawan Sariyoga; Mohamad Arief Setiawan (International Journal of Ethno-Sciences and Education Research, 2021)
Onion is one of the commodities of annual vegetable crops that have high economic value, a type of short-lived plant, can be propagated vegetatively or generatively, can be developed in low to highland areas and can be cultivated throughout the year. High demand for onions was not followed by supply of onion in the market. This is caused by high risks in the cultivation of  Onions. As the theory of supply, the level of supply of a commodity will be affected by the amount of commodities produced. The research aims to analyze the risk factors for onion production and onion supply behavior. The method of this research was survey methode. The location of this research was at Tonjong, Kramatwatu subdistrict. The population of onions farmers was 117 farmers and the amount of the sample used in this research is 54 farmers. Sort of datas that used in this research were primary data and secondary data. The analysis data that used are risk analysis, and multiple linear regression analysis. The results showed that the level of risk of onion in Tonjong Village was 1621.91 or 32 percent of the productivity value obtained by farmers. The source of the risks on Onion farming in Tonjong Village are climate and weather, pests and plant diseases, land fertility, and the effectiveness of using inputs. There are two factors that significantly influence the behavior of onion offering in Tonjong  Village, the cost variable of fungicide and the variable cost of insecticide.